The Effect of Ratio of Old Coconut Water with Soursop Juice and Concentration of Natrium Bicarbonate (NaHCO3) on The Quality of Carbonated Coconut Water - Zulaika Haddis Nasution; Ismed Suhaidi; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The objective of this research was to find out the effect of ratio of old coconut water with soursop juice and concentration of natrium bicarbonate (NaHCO3) on the quality of carbonated coconut water. This research was conducted in December 2015 – January 2016 in the Laboratory of Food Technology, Agriculture Faculty, North Sumatera, Medan, using Completely Randomized Design (CRD) with two factors, i.e. ratio of old coconut water with soursop juice (K) (60%:40%; 70%:30%; 80%:20%; 90%:10%) and concentration of natrium bicarbonate (NaHCO3) (N) (0,4%; 0,5%; 0,6%; 0,7%). The results showed that ratio of old coconut water with soursop juice had highly significant effect on vitamin C content, total acid, pH value, total soluble solid (TSS), ash content, score value of taste, and hedonic value of taste. Concentration of natrium bicarbonate (NaHCO3) had highly significant effect on vitamin C content, total acid, pH value, CO2 content, ash content,  score value of carbonated effect, and hedonic value of taste. The interaction of ratio of old coconut water with soursop juice and concentration of natrium bicarbonate (NaHCO3) had highly significant effect on vitamin C content. Keywords : Carbonated coconut water, natrium bicarbonate, old coconut water, soursop